Pharmacognostical Study and Development of Quality Control Parameters for Cucumis melo Linn - Fahamiya, N.; Aslam, A.; Siddiqui, A.; Shiffa, M.S.M.; Ahmed, A.; Khan, M.S. (American Journal of Pharmtech Research, 2012)
Cucumis melo Linn. (family cucurbitaceae) is extensively cultivated throughout India particularly in the hot and dry North-Western areas. Its fruit pulp, root, seeds and seed oil are used for medicinal purposes. In Unani medicine, the seed kernel is commonly used to treat various disease conditions. Seeds are having diuretic, lithontriptic, laxative, demulcent and refrigerant properties. There are many varieties of melon available and they also show great diversity in foliage. Hence, adultration is very common with this plant. Standardization provides a more reliable, effective and high-quality product by confirming the presence of plant constituents qualitatively and quantitatively. Hence, efforts have been made to standardize the seed to provide scientific data for identification, authentication and distinguishing the plant from its adulterants. The morphological, microscopic, physicochemical and chromatographic studies of Cucumis melo seed will be useful for quality control of this drug in formulations and would serve as a standard reference for further studies
Keywords: Adultration; Cucumis melo; flavonoid; phenolic; standardization